TEACHING MATERIAL DEVELOPMENT LITERATURE AND CULTURE-BASED FOR FOREIGN SPEAKERS INDONESIA - Marwiah Marwiah; Usman Pahar (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
This article presents the results of developing Indonesian culture-based teaching materials. This research refers to the development design that was developed by Dick and Carry (2009): define, design, develop and dessimenate. Teaching material developed has been tested for its validity, effectiveness, and practicality. The results showed the implementation of learning that is, instructional materials compiled and developed feasible to use because it is in the range of values 3.0 M 4.0 .. Aspects of teaching materials towards the achievement of objectives implemented with a mean value of 3.20. The aspect of applying Indonesian culture-based teaching materials was carried out with an average value of 3.05. The context of learning the relevance of Indonesian culture is carried out with a mean value of 3.25. The test result data shows the average value of the acquisition of 82.31 of the 14 students tested. The highest value was 86.20 and the lowest was 73.60. Of the 14 learners who worked on the learning worksheets, 10 people (71.42%) were in the very high category and 4 people (28.58%) were in the high category. So, it was stated that Indonesian language-based learning material was appropriate to be applied to Indonesian language learning for speakers foreign.